2014
DOI: 10.1371/journal.pone.0104380
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Salmonella enterica Serovar 4,[5],12:i:- as a Monophasic Variant of Serovar Typhimurium

Abstract: Salmonella enterica subspecies enterica serovar 4,[5],12:i:- (S. 4,[5]12:i:-) is believed to be a monophasic variant of S. enterica serovar Typhimurium (S. Typhimurium). This study was conducted to corroborate this hypothesis and to identify the molecular and phenotypic characteristics of the S. 4,[5]12:i:- isolates in Japan. A total of 51 S. 4,[5]12:i:- isolates derived from humans, cattle, swine, chickens, birds, meat (pork), and river water in 15 prefectures in Japan between 2000 and 2010 were analyzed. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 29 publications
3
46
0
Order By: Relevance
“…However, S. 4,[5],12:i:‐ has been rapidly increasing in prevalence in recent years. In Japan, Ido et al () detected S. 4,[5],12:i:‐ in isolates from humans and animals, including cattle and swine, from 2000 to 2010, and showed that these isolates consisted of multiple distinct clones that were predominantly pan‐susceptible, with the exception of swine‐derived isolates. Our present study showed that the incidence of S. 4,[5],12:i:‐ has been increasing, thereafter, in Japan in both cattle and swine, and that the resistance rates have also been increasing rapidly, particularly among the bovine isolates.…”
Section: Discussionmentioning
confidence: 99%
“…However, S. 4,[5],12:i:‐ has been rapidly increasing in prevalence in recent years. In Japan, Ido et al () detected S. 4,[5],12:i:‐ in isolates from humans and animals, including cattle and swine, from 2000 to 2010, and showed that these isolates consisted of multiple distinct clones that were predominantly pan‐susceptible, with the exception of swine‐derived isolates. Our present study showed that the incidence of S. 4,[5],12:i:‐ has been increasing, thereafter, in Japan in both cattle and swine, and that the resistance rates have also been increasing rapidly, particularly among the bovine isolates.…”
Section: Discussionmentioning
confidence: 99%
“…The pS24 plasmid isolated from S. enterica 4,12:i:Ϫ had a profile similar to that of S. Typhimurium plasmids, and the parent strain was also isolated from a different swine farm environment. During the last decade, S. enterica 1,4,12:i:Ϫ, 1,4, [5],12:i:Ϫ, and 4,12:i;Ϫ have emerged around the world and have frequently been isolated from human, animal, agricultural production, and environmental sources (37)(38)(39). These serotypes are believed to be a mosaic variant of S. Typhimurium and are related to plasmid-mediated colistin resistance encoded by the mcr-1 gene (37,39,81).…”
Section: Figmentioning
confidence: 99%
“…Human infection by S. enterica serovar 4, [5],12:i:Ϫ (Salmonella 4, [5],12:i:Ϫ), which is believed to be a monophasic variant of Salmonella Typhimurium, has increased considerably since the mid-1990s. This serovar is currently one of the most common serovars in many countries (8)(9)(10)(11)(12) and is responsible for a number of outbreaks, including outbreaks in Luxembourg (13), Germany (14), France (15), and the United States (16). Many of these outbreaks were linked to the consumption of contaminated pork and other sources, such as cattle and poultry (17).…”
mentioning
confidence: 99%
“…Many of these outbreaks were linked to the consumption of contaminated pork and other sources, such as cattle and poultry (17). Isolation of Salmonella 4, [5],12:i:Ϫ from humans and animals has also become common in Japan in recent years (10,18,19). However, the genetic relatedness between isolates in Japan and Western countries is not clear.…”
mentioning
confidence: 99%